Improving Workplace Safety: a Delphi Study on OSH Monitoring and Management - Faragó, Ferenc; Flores Benitez, Fernando René; Szabó, Gyula (INGENIO, 2025)
Improving OSH performance in today’s rapidly changing technological and economic environment is a major challenge for organizations. While there are many studies on OSH practices and interventions, there is little research on the information used by managers to make effective decisions in this area. This study aims to address this by identifying the main sources of information used to make such decisions and the key factors influencing them. A 16-person panel of OSH professionals and managers were asked in three rounds of the Delphi method for their views. In the first round, they provided qualitative feedback on information sources and factors that influence decisions. These were analysed and used to create questions for the next rounds. A 70% agreement threshold was used to determine consensus. The panel agreed on four key sources of information for OSH decisions: compliance, employee feedback, risk assessments, and accident analysis results. The study identified influential factors affecting how this information is interpreted, including organisational culture, leadership commitment and resource availability. Effective OSH decision-making also depends on broader contextual and organisational factors, not just information availability.